The Influence Of Taste And Product Varıance On Purchase Decısıon Of Mıe Gacoan Madıun - Rizal Ula Ananta Fauzi; Zakia Intan Dyah Permata; Hendra Setiawan (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This research aims to identify and analyze the influence of several factors on the purchasing decision of Mie Gacoan Madiun. The factors under investigation are product taste, product variety, The research employed a survey method, distributing questionnaires to respondents who are consumers of Mie Gacoan Madiun in a specific region. Data collection was carried out through interviews and online questionnaires. Subsequently, the gathered data were analyzed using multiple linear regression to examine the relationship between the independent variables (product taste, product variety,) and the dependent variable (purchasing decision).The results of the study indicate that product taste, product variety, significantly influence the purchasing decision of Mie Gacoan Madiun. Unique product taste and diverse product variety attract consumers' interest in buying Mie Gacoan.. This research provides insights for Mie Gacoan Madiun businesses to devise more effective marketing strategies. By considering the mentioned factors, it is hoped that they can enhance product appeal and increase customer loyalty. Furthermore, this study can serve as a reference for further research in the field of food and beverage marketing to delve deeper into consumer preferences and the factors influencing purchasing decisions.